Penerapan Syari'ah Islam dalam Negara Bangsa di Indonesia - Muhammad Al Faruq (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Islamic movements that make Islam as an ideology, both at national and global levels always lead to aspirations and demands to implement shari'ah (Islamic law) in total (kaffah) through State instruments. In a legal country like Indonesia, such aspirations and demands cannot always be fulfilled. This is because the rule of law like Indonesia, from the very beginning was built on the basis of the spirit of nationalism based on principles, divinity, humanity, justice, unity and the principle of equality or equality of every citizen in front of the law.